Victim reparation under the Ius Post Bellum : an historical and normative perspective / Shavana Musa. - Musa, Shavana (Cambridge studies in international and comparative law ;, 2019)
Victim Reparation under the Ius Post Bellum fills an enormous gap in international legal scholarship. It questions the paradigmatic shift of rights to reparation towards a morality-based theory of international law. At a time when international law has a tendency to take a purely positivistic and international approach, Shavana Musa questions whether an embrace of an evaluative approach alongside the politics of war and peace is more practical and effective for war victims. Musa provides a never-before-conducted contextual insight into how the issue has been handled historically, analysing case studies from major wars from the seventeenth century to the modern day. She uses as-yet untouched archival documentation from these periods, which uncovers unique data and information on international peacemaking, and actually demonstrates more effective practices of reparation provisions compared with today. This book combines historical analysis with modern day developments to provide normative assertions for a future reparation system.